Relacja kroniki Stefana Ranatowicza CRL (1617-1694) na temat biogramów prepozytów klasztoru Bożego Ciała Kanoników Regularnych Laterańskich Kongregacji Krakowskiej (od Konrada Alemana do Wiktoryna Wereszczyńskiego) - Pęgier, Małgorzata (Saeculum Christianum. Pismo Historyczne, 2016)
The presented article is a discussion of biographies of 13 subsequent provosts of the monastery of Canons Regular of Lateran of Krakow Congregation, at the Corpus Christi church in Kazimierz district. The author of the chronicle, father Stefan Ranatowicz, lived in the years 1617-1694, in Kazimierz near Krakow, where he learned at the parish school at the Corpus Christi church and studied at the Krakow Academy (in the years 1635-1636). In the autumn of 1636, he joined the congregation of Canons Regular of Lateran. He was one of the leading historiographers of his order. His most important work is the Chronicle with the Latin title: Casimiriae civitatis, urbi Cracoviensi confrontatae, origo. in eaque ecclesiarum erectiones et religiosorum fundationes, nec non series, vitae, res gestae praepositorum Conventus Canonicorum Regularium Lateranensium S[ancti] Augustini ad Ecclesiam S[acratis]S[imi] Corporis Christi descriptae a Stephano Ranothowicz eiusdem conventus et Ecclesiae Canonico Regul[ari] professo. Its main section contains biographies of provosts of the Krakow monastery, from Konrad Aleman to Wiktoryn Wereszczyński. Apart from topics related directly with monastic matters, the author also discussed many issues relating to daily, religious, as well as cultural life of Kazimierz and Krakow, and also often mentioned social and economic matters concerning also the entire Polish State.